Image reconstruction of TGZ3 grating by eliminating tip‐sample convolution effect in AFM. (30th December 2020) - Wu, Teng; Lv, Luyao; Zou, Yu; Han, Guoqiang
Abstract : Accurate and meticulous measurement is an important prerequisite to obtain the real surface information of samples in atomic force microscopy (AFM). A severe problem is the frequent occurrence of measurement errors, which are mainly caused by the nonlinearity of the probe driver, the temperature drift of the system and the tip characteristics. The measurement errors caused by probe tip are the main source of errors in AFM nanoscale measurements. The shape and state of AFM tip will distort the AFM image from the actual sample morphology. If the information about the probe is known, the measurement error caused by the probe tip can be greatly reduced. In order to obtain accurate AFM images, a new method based on geometric measurement model and blind tip reconstruction is proposed to eliminate tip‐sample convolution in the measurement of grating samples. The static and dynamic characteristics of the AFM tip are described by four parameters: cone angle, curvature radius, scanning inclination angle and mounting inclination angle. Finally, the feasibility and effectiveness of the new calibration method are verified by evaluating the image reconstruction quality. In conclusion, the proposed method can effectively reconstruct accurate AFM images of the grating.